Designing a Web-Based Management Information System in the Kerupuk Puli Dua Bintang Cracker Industry in Tulungagung Regency - Ulfa Emi Rahmawati; Puji Hastuti; Raditya Arief Pratama; Qonitatul Hasanah; Wahyu Kurnia Dewanto (Nusantara Science and Technology Proceedings, 2022)
Nowadays, there are many changes in the field of Information Technology, from simple communication to electronic communication. This development affects several sectors of the world. The industrial world today is influenced by the development of information technology and makes the management information system in the management of information in the industry. A management Information System is a collection of information systems that are willing to interact and responsible for processing and collecting information data so that they can assist and manage at all levels when planning and managing activities. The Kerupuk Puli Dua Bintang Cracker Industry is in Tulungagung Regency, a small, micro, small, and medium enterprise (MSME), and still mandates data management in manual management. The use of manual management can cause various problems that should not occur. For example, data loss due to lost or torn books. As well as log data searches due to extensive production activities, inaccurate calculations, incorrectly entering data related to the production process, and other unlucky things that can interfere with production in the Kerupuk Puli Dua Bintang Cracker Industry. This research designs a Management Information System to facilitate information management and solve the errors caused by UML (Unified Modeling Language) diagrams. The research method used in the study uses a descriptive method. Namely, using this method to comprehensively depict the Kerupuk Puli Dua Bintang Cracker industry to find problems. The result of this research is the design of a Web-based Management Information System to assist in managing and developing businesses in the Kerupuk Puli Dua Bintang Cracker Industry. Research can for building a web-based Management Information System by design.